Calidad de vida en 2010 - Velázquez, Guillermo Ángel (2020)
Quality of life, unlike poverty, is a measure of achievement against a level that has been set as "optimal". For the analysis of quality of life, three common socio-economic dimensions have been considered, which are widely recognised and present in the public agenda: housing, health and education. Environmental elements are also incorporated. The latter are broken down, on the one hand, into traditional environmental problems - flooding, seismicity, the presence of rubbish dumps, pollution - and on the other, into recreational resources specific to each environment, which may have a "natural base" - those provided by nature, but transformed by society - or be totally artificial - that is, socially constructed, such as sports, cultural or commercial centres. These dimensions (socioeconomic and environmental) are approximated by selecting variables and then translating them into index numbers to ensure comparability. The values of the quality of life index for 2010 can be visualised by means of maps in different geographical units. The analysis of the results shows marked differences between the various regions, provinces and the departments, parties or communes that make them up, especially when factors such as: migratory dynamics, centrality and accessibility, urban scale, available wealth and public policies at different levels, among others, are taken into account.